Birds of Sierra Hermosa Ecological, Tourist and Recreational State Park, State of Mexico - Bautista-Trejo, Rogelio; Ramírez-Hernández, Monserrat; Gómez-Garduño, J. Oswaldo; Valverde-Nieto, Juan G.; Cayetano-Rosas, Héctor; Piñón-Santoyo, Neptalí; J. Pedro Cabañas-Pérez, J. Pedro Cabañas-Pérez; Ramirez-Albores, Jorge E. (Ecosistemas y Recursos Agropecuarios, 2023)
Greenspaces immersed in the large urban centers serve as shelters for biodiversity, reducing the negative impact of urbanization. To contribute to the knowledge of the avifauna of central Mexico, in the present study the bird diversity presents in the Sierra Hermosa Ecological, Tourist and Recreational State Park, a peri-urban area of the Metropolitan Area of Mexico City was determined, adjacent to the new international airport. The data was obtained by carrying out field work over 29 months of sampling between 2019 and 2022. A total of 199 bird records were obtained, belonging to 46 families and 17 orders. The families that presented the highest species richness were Tyrannidae (19) and Parulidae (14). Ninety-two resident, 95 migratory and 12 introduced species were found. The most representative trophic group was that of insectivores (115) and the habitat with the highest species richness was abandoned buildings with induced trees (92). Three endemic species and six under some risk categories were found according to NOM-059-SEMARNAT-2010. According to the results, this park is a site of great importance for feeding, shelter and reproduction for populations of resident and migratory birds that inhabit the periphery of the urban area, and that in the local scenario could be used for future research on rehabilitation, restoration, and territorial planning in the Valley of Mexico.